2018
DOI: 10.48550/arxiv.1812.00309
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The directed landscape

Abstract: The conjectured limit of last passage percolation is a scale-invariant, independent, stationary increment process with respect to metric composition. We prove this for Brownian last passage percolation. We construct the Airy sheet and characterize it in terms of the Airy line ensemble. We also show that last passage geodesics converge to random functions with Hölder-2/3 − continuous paths. This work completes the construction of the central object in the Kardar-Parisi-Zhang universality class, the directed lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
222
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(226 citation statements)
references
References 39 publications
4
222
0
Order By: Relevance
“…A path on which the total weight is attained is called a geodesic from x to y. Lattice LPP belongs to a large family of LPP models which seem to share the same limiting behaviour of the fluctuations of their observables. Since the seminal work of Rost [36] where the first order of L(0, y) was established for y large in exponential LPP, much progress has been made in the study of these models [1,13,26,28,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A path on which the total weight is attained is called a geodesic from x to y. Lattice LPP belongs to a large family of LPP models which seem to share the same limiting behaviour of the fluctuations of their observables. Since the seminal work of Rost [36] where the first order of L(0, y) was established for y large in exponential LPP, much progress has been made in the study of these models [1,13,26,28,35].…”
Section: Introductionmentioning
confidence: 99%
“…The sup functional in (1.1) takes two elements, L and h ρ . In [13,14] it was shown that under the KPZ scaling, for various LPP models, L has a limiting object L called the Airy Sheet. If the process h has a diffusive scaling limit G, and if the sup functional is continuous with respect to the topologies in which the convergences take place, then one would hope that the limit of H N will be given by…”
Section: Introductionmentioning
confidence: 99%
“…The terminology comes from the fact that last passage percolation can essentially be thought of as a metric on the plane. When the environment is a collection of independent two-sided Brownian motions B = {B i ∶ i ∈ Z}, the Brownian last passage percolation (x, m; y, n) ↦ B[(x, m) → (y, n)] has a four-parameter scaling limit, recently constructed in [9]. This limit is the directed landscape L. More recently, L was shown to be the scaling limit of other integrable models of last passage percolation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Our overall techniques for proving Theorem 1.4 heavily relies on the inputs from the Gibbs property of the KPZ line ensemble (via Proposition 4.6 and 4.7) and monotonocity property of the KPZ equation (via Proposition 4.8). Such properties are also present in many models in the KPZ universality class including the KPZ fixed point (recently constructed in [MQR16,DOV18]), asymmetric simple exclusion process (ASEP), last passage percolation, stochastic six vertex model etc. We hope that it could be possible to prove lower bound to the lower tail probability of those models using the techniques of the present paper.…”
Section: Introductionmentioning
confidence: 98%